PENGARUH PENERAPAN METODE PENILAIAN PERSEDIAAN TERHADAP LABA PERUSAHAAN DENGAN PERHITUNGAN BIAYA PRODUKSI PADA PT SUMBER ALAM PONTIANAK - B51112005, Melly Susanti (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
The research aims to examine the the effect of the application of the inventory valuation method on corporate earnings with the calculation of production costs. Data used are primary data from reports of raw material purchase PT Sumber Alam Pontianak in 2014. The research uses computerized calculations and analyzed with simple regression analysis statistical methods to analyze the data with 5% significance level. Research hypothesises are tested by F-test and R-squared. R-squared result implies that the inventory valuation method does not provide a significant positive effect on corporate profits. F-test results showed that the independent variables are not simultaneous and significant influence on the dependent variable. Based on the F-test found that First In First Out variable significant negative effect on corporate pofits, Last In First Out variable significant negative effect on corporate profits and the average variable significant negative effect on corporate profits. Variability of inventory valuation method have a significance level above 5%. This indicates that these variables were not significant negative effect on corporate profits. Keyword : corporate profits, inventory valuation method